The Porcellanidae (Crustacea: Decapoda: Anomura) of the Red Sea with description of a new species of Petrolisthes - Werding, Bernd; Hiller, Alexandra (Zootaxa, 2007)
The porcellanid crabs from the Red Sea are revised based on museum collections. A complete compilation of all species known from the Red Sea is presented, including four new records of species for that region. Petrolisthes aegyptiacus n. sp. is described on the basis of an old collection of porcellanids from the Museum für Naturkunde, Stuttgart. The presence of Petrolisthes lamarckii in the Red Sea is confirmed and a single specimen, which corresponds in its general characters to Petrolisthes donanensis from Japan, is reported. Porcellanella haigae is reported based on photographs from a field guide. As a result, 18 species are now known to occur in the Red Sea. Figures of all known species are included and an identification key to the species is provided.